From dungeon to haven: competing theories of gestation in Leviticus Rabbah and the Babylonian Talmud - Schick, Shana Strauch (AJS review, 2019)
Rabbinic literature offers competing images of embryology and the relationship between mother and fetus. The Palestinian midrashic collection Leviticus Rabbah 14 marginalizes the active role of the mother and depicts the process of gestation as a dangerous time for the fetus. God is in charge of the care and birth of the child, and the father is the lone source of physical material. Passages in the third chapter of Bavli tractate Niddah, in contrast, reference the biological contributions of the mother and portray an idyllic image of the womb. This study explores how cultural differences, variances in representations of women, and sources of authoritative medical knowledge in Sasanian Persia and Roman Palestine contributed to the formation of these texts with markedly different understandings of the relationship between mother and fetus. I will argue that the study of the Sasanian Persian context is key to understanding the Bavli motifs, but that the Palestinian sources can best be understood with references not only to contemporaneous Greco-Roman sources, but also to ancient Iranian and Mesopotamian works, which have been generally overlooked by scholars.